Hospital Marketing Strategies to Increase the Number of Patient Visits - M Miladi Fauzan; Agustinus Purna Irawan (Danadyaksa: Post Modern Economy Journal, 2026)
The healthcare industry in Indonesia is facing increasingly intense competitive pressures, particularly in urban areas. According to data from the Indonesian Ministry of Health (2023), the total number of hospitals in Indonesia has reached more than 3,100, with the number of private hospitals increasing to more than 1,900. This growth forces each healthcare facility to develop more adaptive and data-driven marketing strategies. However, most hospitals, especially those in the middle to lower scale, still rely on conventional marketing approaches that have not optimally utilized digital platforms as communication channels for patients. This study aims to analyze the influence of hospital marketing strategies on the number of patient visits, focusing on three main variables: (1) digital promotion and marketing strategies, (2) service quality based on the 7P marketing mix, and (3) patient experience, as well as the mediating role of online reputation and patient trust. Patient experience in this study is operationally defined as the quality of service interactions perceived by patients, including the service process and staff interactions, while online reputation is defined as digital-based public perception formed through online reviews, ratings, and testimonials. The study uses a quantitative approach with an explanatory research design, namely the collection and analysis of quantitative data from structured surveys using a Likert-scale questionnaire for patients. Quantitative data analysis used the Structural Equation Modeling–Partial Least Squares (SEM-PLS) model. The expected outcome of this study is the formation of a strategic model that explains the relationship between hospital marketing variables and patient visits, while also generating practical recommendations for hospital management in designing effective, sustainable, and responsive marketing strategies to patient needs in the digital era.